Gibt es ein Europäisches Verwaltungsrecht? Vortrag vom 08. Januar 2010 im Rahmen einer Veranstaltung des Vereins zur Förderung der Europäischen Rechtslinguistik e.V. an der Universität zu Köln - Mann, Thomas (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2011)
This work utilizes examples from the jurisprudence of the European Court of Justice (ECJ) to illustrate the growing trend toward universal European Administrative law, despite the existing rule that member states must enforce community law through their national administrative law. The paper initially explores the impact of the principles of effectiveness and non-discrimination as the basis of enforcement of administrative law at the national level. It then moves onto an analysis of the principles of proportionality, legitimate expectation and legal certainty, as these are equally relevant to the uniform application of administrative law in the Member States. Lastly, the author affirms and illustrates, through the development of law brought about by the ECJ, the movement towards a consistent growth in European Administrative Law.